2012
DOI: 10.1039/c2dt31133j
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and structural characterization of novel cyclam-based zirconium complexes and their use in the controlled ROP of rac-lactide: access to cyclam-functionalized polylactide materials

Abstract: Novel Bn(2)Cyclam-based zirconium complexes of the type (Bn(2)Cyclam)Zr(X)(X') (3, X = X' = OPh; 4, X = X' = SPh; 5, X = Cl, X' = O(i)Pr) were synthesized in good yields via metathesis routes involving the reaction of the dichloro precursor (Bn(2)Cyclam)Zr(Cl)(2) and the appropriate lithium salts. The molecular structures of compounds 3, 4 and 5, as determined by X-ray crystallographic studies, all confirmed the effective chelation of the Bn(2)Cyclam ligand in a κ(4)-N(2)N(2)' fashion, with the hexa-coordinate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
22
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 27 publications
(26 citation statements)
references
References 115 publications
4
22
0
Order By: Relevance
“…It provided irrefutable proof of an octadentate coordination environment where all four macrocycle nitrogen atoms and acetate pendant arms participated in Zr 4+ ion coordination. Furthermore, the compressed, square anti-prismatic geometry and low-symmetry saddle-like ligand conformation displayed by Zr- 37 was consistent with the limited number of reports describing Zr-catalysts containing analogous ligands with a Zr(IV) metal center that lacks crystal-field stabilization [ 120 , 121 , 122 , 123 , 124 , 125 , 126 , 127 , 128 ].…”
Section: The Rationale For New Zirconium-89 Chelation Strategiessupporting
confidence: 84%
“…It provided irrefutable proof of an octadentate coordination environment where all four macrocycle nitrogen atoms and acetate pendant arms participated in Zr 4+ ion coordination. Furthermore, the compressed, square anti-prismatic geometry and low-symmetry saddle-like ligand conformation displayed by Zr- 37 was consistent with the limited number of reports describing Zr-catalysts containing analogous ligands with a Zr(IV) metal center that lacks crystal-field stabilization [ 120 , 121 , 122 , 123 , 124 , 125 , 126 , 127 , 128 ].…”
Section: The Rationale For New Zirconium-89 Chelation Strategiessupporting
confidence: 84%
“…This is not unusual, since Zr tetraazamacrocycle complexes exhibit varying geometries dictated by the additional ligands that occupy the coordination sites not occupied by the nitrogen atoms of the macrocycle. 25,26,28 The perpendicular distance from the metal center to the plane described by the 4 acetate-containing pendant arms of the macrocycle is 1.004(3) Å, and the perpendicular distance from the metal center to the plane described by the 4 nitrogens of the macrocycle is 1.310(4) Å. The DOTA ligand displays a low-symmetry saddle-like conformation similar to that of metal–dibenzotetramethytetraaza[14]annulene complexes described by De Angelis and co-workers.…”
Section: Resultsmentioning
confidence: 99%
“…29 The average Zr–ligand bond lengths and bond angles are comparable to those observed in structurally characterized Zr complexes containing hydroxamate, phenoxyamine, salophen, or cyclam ligands. 25,26,28,3033 …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Apart from a pioneering study by Montaudo et al from 1996, similar observations are mostly only briefly reported for other alkoxide complexes used as catalysts for lactide polymerization. Apparently, the metal ion does not have a large impact, since these complexes described in literature are based on actinoides, alkali metals, alkaline earth metals, titanium, zirconium, and zinc . The only exceptions from this trend seems to be an aluminum catalyst with a sterically demanding multidentate salen‐type ligand and a zinc catalyst that was applied without addition of an alcohol as co‐initiator.…”
Section: Resultsmentioning
confidence: 99%